2020
DOI: 10.37418/amsj.9.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Application of Adomian Decomposition Method on a Mathematical Model of Malaria

Abstract: In this paper, we consider a deterministic model of malaria transmission. Adomian decomposition method (ADM) is used to calculate an approximation to the solution of the non-linear couple of differential equations governing the model. Classical fourth-order Runge-Kutta method implemented in Maple18 confirms the validity of the ADM in solving the problem. Graphical results show that ADM agrees with R-K 4. In order words, these produced the same behaviour, validating ADM's efficiency and accuracy of ADM in findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In recent times, a variety of mathematical models have been developed to investigate the transmission dynamics of COVID-19; for examples, see [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] and the references listed therein. Malaria mathematical models are also thoroughly examined in [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] and references are mentioned. Infected individuals with SARS-CoV-2 who live in malaria-endemic regions run the risk of developing severe COVID-19 or adverse disease outcomes if they fail to take care of their malaria condition.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, a variety of mathematical models have been developed to investigate the transmission dynamics of COVID-19; for examples, see [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] and the references listed therein. Malaria mathematical models are also thoroughly examined in [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] and references are mentioned. Infected individuals with SARS-CoV-2 who live in malaria-endemic regions run the risk of developing severe COVID-19 or adverse disease outcomes if they fail to take care of their malaria condition.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the series solution converged very fast and the solutions were accurate. The Adomian Decomposition Method (ADM) was used to solve the mathematical model of malaria in [2]. The Laplace Adomian Decomposition Method (LADM) was applied to analyse the SEIR epidemic models of measles in reference [3].…”
Section: Introductionmentioning
confidence: 99%